Fast Food Consumption and Academic Growth in Late Childhood. (August 2015) - Purtell, Kelly M.; Gershoff, Elizabeth T.
Objective . The objective of this study is to examine the associations between fast food consumption and the academic growth of 8544 fifth-grade children in reading, math, and science. Method . This study uses direct assessments of academic achievement and child-reported fast food consumption from a nationally representative sample of kindergartners followed through eighth grade. Results . More than two thirds of the sample reported some fast food consumption; 20% reported consuming at least 4 fast food meals in the prior week. Fast food consumption during fifth grade predicted lower levels of academic achievement in all 3 subjects in eighth grade, even when fifth grade academic scores and numerous potential confounding variables, including socioeconomic indicators, physical activity, and TV watching, were controlled for in the models. Conclusion . These results provide initial evidence that high levels of fast food consumption are predictive of slower growth in academic skills in a nationally representative sample of children.